AMPLIFIER ANALYSIS OF RADIO OVER FIBER COMMUNICATION SYSTEMS - Kazancili, Ugur Umur; Unverdi, N. Ozlem (YILDIZ TECHNICAL UNIV, 2019)
This study focuses on radio communication systems over fiber (ROF). In the design of these systems, optical source, pulse generator, modulator, optical fiber, optical add-drop multiplexer (OADM), amplifier, filter were used. The amplifiers were examined and their performance analyses were done on the OptiSystem 7.0 simulation software. Radio over fiber system is modeled with different types of amplifiers. Effects of optical amplifiers on the system were analyzed. The amplifiers were compared to determine the most suitable amplifier for the radio over fiber.
Keywords: Communication technologies; optical communications; ROF; amplifier; optical fiber; EDFA; Engineering